Enhancing Competence in Critical Thinking, Creativity, Collaboration, and Communication in the New Normal Era - Herlina, Eka; Kamila, Isti; Sara, Siti Aisah (Jurnal Pengabdian Masyarakat Inovatif, 2023)
The COVID-19 pandemic (coronavirus disease 2019) has caused various problems in terms of health, education, economy, and other aspects. Vitamins are a complex compound that is needed by the body both for immunity and sharpening focus, especially during this pandemic. Therefore, in this social empowerment, the time conducted counseling on the importance of vitamins to teachers, parents, and students of SD Negeri Court 2. The Covid-19 pandemic has also had an impact on students' 4C (Critical Thinking, Communication, Collaboration and Creativity) skills. To overcome this, the members of the social empowerment also conducted learning by using integer chip props to hone students' 4C skills. Through the collaboration of chemistry study program lecturers who provide socialization of the importance of vitamins and mathematics study program lecturers who provide teaching integer operations with integer chip. By this social empowerment activities, students can focus on observing the learning process and honing students' 4C skills.